2003
DOI: 10.1161/01.cir.0000074225.62168.68
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Granulation Tissue Cell Apoptosis During the Subacute Stage of Myocardial Infarction Improves Cardiac Remodeling and Dysfunction at the Chronic Stage

Abstract: Background-Granulation tissue cells at the subacute stage of myocardial infarction (MI) are eliminated by apoptosis to finally make a scar at the chronic stage. We hypothesized that postinfarct inhibition of apoptosis might preserve myofibroblasts and endothelial cells in granulation and modulate chronic left ventricular (LV) remodeling and heart failure. Methods and Results-A pancaspase inhibitor, Boc-Asp-fmk (BAF, 10 mol/kg per day), or vehicle (control) was given to rats with experimental large MI. The trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
77
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 27 publications
5
77
0
Order By: Relevance
“…The difference in the proportions of cardiomyocyte apoptosis have been reported in the previous studies, 10,[29][30][31] and the difference between the studies might have been due to differences in the tissue samples taken or the method used for analysis of myocardial tissue. 7,32 However, a previous literature by van Empel et al reviewed a prevalence of cardiomyocyte apoptosis ranging from 0.12 to 0.70% in myocardial biopsy specimens obtained from patients with NYHA classes III-IV heart failure, 30,[33][34][35][36][37][38][39][40] which was similar to the figure obtained in the present study. Therefore, the variation in the prevalence of cardiomyocyte apoptosis between the reported studies may not have been due to differences in the myocardial tissue samples used for analysis.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The difference in the proportions of cardiomyocyte apoptosis have been reported in the previous studies, 10,[29][30][31] and the difference between the studies might have been due to differences in the tissue samples taken or the method used for analysis of myocardial tissue. 7,32 However, a previous literature by van Empel et al reviewed a prevalence of cardiomyocyte apoptosis ranging from 0.12 to 0.70% in myocardial biopsy specimens obtained from patients with NYHA classes III-IV heart failure, 30,[33][34][35][36][37][38][39][40] which was similar to the figure obtained in the present study. Therefore, the variation in the prevalence of cardiomyocyte apoptosis between the reported studies may not have been due to differences in the myocardial tissue samples used for analysis.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, another study has recently shown that inhibition of apoptosis in granulation tissue in the infarcted region formed thicker walls, which contributed to ventricular remodeling. 7 Although the time course and type of apoptosis varies in patients with heart failure, the lack of stage-specific expression of granulation tissue apoptosis in the present study indicates that antiapoptotic therapy in patients with heart failure might have profound effects on inhibiting apoptosis in cardiomyocytes, leading to a decrease in ventricular remodeling and heart failure. 44 In the present study, the temporal and spatial distribution of TNF-a-positive cardiomyocyte differed from that of ss-DNA-positive cardiomyocyte; the mean SI of cardiomyocytes peaked at stage II and then declined rapidly, whereas the mean TI peaked at stage III and remained constant well into the later stages, as similarly reported previously.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations